Propiedades electromagnéticas de un compuesto magneto dieléctrico a través de un algoritmo basado en el método Nicolson-Ross-Weir (2021)
The present work implements the Nicolson-Ross-Weir (NRW) method to find the permittivity and permeability through an algorithm in Matlab® of a magneto - dielectric composed material made of polyester resin and magnetite powders randomly dispersed and oriented vertically and horizontally in the polymeric matrix. The measured data come from the simulation of the S parameters in ADS® between 150 kHz and 4GHz, on a microstrip type transmission line. The algorithm allowed to verify that the best response in high frequency of the magneto - dielectric composed where the vertically orientedparticles, present the highest relative permittivity obtaining Er= 5.5 for 30% wt concentration and Er= 4.5 concentration of 20% wt, with an absorption coefficient which increases in function of frequency and the concentration of magnetite in the functional filler.